133CS AND 35CL NMR SPECTROSCOPY AND MOLECULAR DYNAMICS MODELING OF CS+ AND CL- COMPLEXATION WITH NATURAL ORGANIC MATTER - Xu X.; Kalinichev A.G.; James Kirkpatrick R. (My University, 2006)
Interaction of dissolved aqueous species with natural organic matter (NOM) is thought to be important in sequestering some species and enhancing the transport of others, but little is known about these interactions on a molecular scale. This paper describes a combined experimental 133Cs and 35Cl nuclear magnetic resonance (NMR) and computational molecular dynamics (MD) modeling study of the interaction of Cs+ and Cl- with Suwannee River NOM. The results provide a detailed picture of the molecular-scale structure and dynamics of these interactions. Individual NOM molecules are typically hundreds to thousands of Daltons in weight, and on the molecular scale their interaction with small dissolved species can be investigated in ways similar to those used to study the interaction of dissolved aqueous species with mineral surfaces. As for such surface interactions, understanding both the structural environments and the dynamics over a wide range of frequencies is essential. The NMR results show that Cs+ is associated with NOM at pH values from 3.4 ± 0.5 (unbuffered Suwannee River NOM solution) to 9.0 ± 0.5. The extent of interaction increases with decreasing CsCl concentration at constant pH. It also decreases with increasing pH at constant CsCl concentration due to pH-dependent negative structural charge development on the NOM caused by progressive deprotonation of carboxylic and phenolic groups. The presence of NOM has little effect on the 133Cs chemical shifts, demonstrating that its local coordination environment does not change significantly due to interaction with the NOM. Narrow, solution-like line widths indicate rapid exchange of Cs+ between the NOM and bulk solution at frequencies of >102 Hz. The MD simulations support these results and show that Cs+ is associated with the NOM principally as outer sphere complexes and that this interaction does not reduce the Cs+ diffusion coefficient sufficiently to cause NMR line broadening. The 35Cl NMR data and the MD results are consistent in demonstrating that there is no significant complexation between Cl- and NOM in the pH range investigated, consistent with negative structural charge on the NOM. © 2006 Elsevier Inc. All rights reserved.